2018
DOI: 10.11648/j.ijmsa.20180701.13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lead Additions on Microstructure and Casting Properties of AZ91 Magnesium Alloy

Abstract: In this study, the effect of Pb element addition varied between 0.2-0.4 wt.% on the microstructure and casting properties of AZ91 magnesium alloy were investigated. The microstructural results showed that as increasing Pb additions into the AZ91 alloy, the grains and the Mg 17 Al 12 intermetallic phase becomes thinner. When examining the effect on casting properties; It was observed that the fluidity of AZ91 alloy increased as the increasing of Pb additions. In the hot tear tests two different mold systems wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…[16], suggested that the corrosion resistance of magnesium alloys can be controlled by microstructure properties such as grain size or secondary phases. it has also been proven by some studies [17][18][19][20] that it has an important role in the development of microstructure control Mg alloys. (zengin at al.)…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…[16], suggested that the corrosion resistance of magnesium alloys can be controlled by microstructure properties such as grain size or secondary phases. it has also been proven by some studies [17][18][19][20] that it has an important role in the development of microstructure control Mg alloys. (zengin at al.)…”
Section: Introductionmentioning
confidence: 94%
“…Mg 2+ is abundant in the human body and takes an active role in many metabolic reactions and biological mechanisms [4]. Furthermore, the Young's modulus of magnesium (41)(42)(43)(44)(45) is closer to the natural bone (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) than that of iron (~211.4 GPa) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum-containing magnesium alloys (AZ, AM, AS series) have become particularly attractive for aviation and automotive industries due to their low density. In fact, the AZ series Mg alloys contain intermetallic particles Mg 17 Al 12 , known as β-phase [2,5]. Mg is chemically active and its corrosion resistance in aqueous media is not good, despite its excellent properties such as high specific strength, suitable for high pressure die-casting, good castability [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, comprehension of the mechanism of the corrosion process which is effected by the secondary phases such as Mg 17 Al 12 and MgZn in Mg-Al-Zn alloys, is of great importance in the field of alloy development, microstructure, mechanical properties and corrosion studies. According to the literature, particularly AZ91 Mg alloy corrosion studies, the amount and distribution of Mg 17 Al 12 secondary phases have a significant effect on the corrosion behavior of AZ91 Mg alloy [3][4][5][6] They have shown that the secondary phase (Mg 17 Al 12 phase in AZ91) causes both micro-galvanic acceleration of the corrosion of the matrix α-phase and also acts as a barrier on the corrosion process and prevents the progression of the matrix α-phase corrosion. The purpose of this study is to investigate the corrosion behavior of β-Mg 17 Al 12 intermetallic phase compared with pure Mg. * e-mail: ekoc@karabuk.edu.tr…”
Section: Introductionmentioning
confidence: 99%